Impact of Different Dental Implant Alloys and Coating Materials on the Health of Tissues Surrounding Implants: a Systematic Literature Review - Ksenija Matvijenko; Alma Pranckeviciene; Rokas Borusevicius (Stilus Optimus, 2024)
Objectives: Recently surface modification techniques have been introduced to dental implants to improve osseointegration, bone formation at the implant surface, and to reduce the occurrence of mucositis and peri-implantitis. The aim of this systematic literature review was to investigate the dependence of the risk of inflammation of the tissues surrounding the implant on different implant alloys and surface coating materials. Material and Methods: The search for the systematic review of the scientific literature was performed between November 28, 2023, and February 5, 2024. Articles were retrieved using the PRISMA screening system from MEDLINE (PubMed), EMBASE (ScienceDirect), Cochrane Central Register of Controlled Trials (the Cochrane Library), Springer Link, and Google Scholar databases. The literature review included publications in English, randomized controlled clinical trials assessing bleeding on probing, pocket depth, and marginal bone level around the implant. Results: A total of 41 full-text articles were selected after removing duplicates, of which 5 were included in this systematic literature review. The data from the studies were structured and presented in summary tables. Statistically significant differences in marginal bone level loss were observed using fluoride and sandblasting with large grit and acid-etching methods for implant surface modification. However, the effects of other surface coating materials and different implant alloys on bone loss, bleeding on probing, and pocket depth were not found to be significant. Conclusions: Despite the limitations of this literature review, it can be concluded that implant alloys and surface coating materials are potential risk factors for the development of inflammation in the tissues surrounding the implant.